Fatores que dificultam a dinâmica de ensino - aprendizagem nos anos iniciais do ensino fundamental no contexto educacional do município de Tomé-Açu/PA - NASCIMENTO, Glenda Yessa Telles (2023)
This course conclusion work is born from the need to study and describe the factors of learning difficulties in reading and writing in the initial series of elementary school I in Tomé-açu/PA, aiming to describe the main factors that cause the difficulties of reading and writing learning of elementary school students, in addition to pointing out in which situations these difficulties occur, and which are the most recurrent ones presented by the students. Since this is a subject of great relevance, as it is essential and indispensable that there is a good development in the learning of reading and writing of the students, especially in the early years, as this learning will contribute to their development during their interactions with their environment. both school and social. Therefore, seeking to work with the learning difficulties presented in Elementary School I, understood as an alternative for improving teaching, learning and student development. Considering that each subject learns in a different way and time from one another. To support this research, we will use studies of altars that see corroborate with the theme. The methodology adopted in this field research will be of a qualitative nature, based on bibliographic studies, having as a data collection technique the observation and analysis of reading and writing practices in the classroom. With this we can highlight the main situations and factors that lead to reading and writing difficulties in Elementary School students. of the family, so that there is success in the teaching-learning process of each student and their specificity in the way they learn and develop.